Effectiveness of 4% chlorhexidine umbilical cord care on neonatal mortality in Southern Province, Zambia (ZamCAT): a cluster-randomised controlled trial. Issue 11 (November 2016) - Semrau, Katherine E A; Herlihy, Julie; Grogan, Caroline; Musokotwane, Kebby; Yeboah-Antwi, Kojo; Mbewe, Reuben; Banda, Bowen; Mpamba, Chipo; Hamomba, Fern; Pilingana, Portipher; Zulu, Andisen; Chanda-Kapata, Pascalina; et al.
Summary: Background: Chlorhexidine umbilical cord washes reduce neonatal mortality in south Asian populations with high neonatal mortality rates and predominantly home-based deliveries. No data exist for sub-Saharan African populations with lower neonatal mortality rates or mostly facility-based deliveries. We compared the effect of chlorhexidine with dry cord care on neonatal mortality rates in Zambia. Methods: We undertook a cluster-randomised controlled trial in Southern Province, Zambia, with 90 health facility-based clusters. We enrolled women who were in their second or third trimester of pregnancy, aged at least 15 years, and who would remain in the catchment area for follow-up of 28 days post-partum. Newborn babies received clean dry cord care (control) or topical application of 10 mL of a 4% chlorhexidine solution once per day until 3 days after cord drop (intervention), according to cluster assignment. We used stratified, restricted randomisation to divide clusters into urban or two rural groups (located <40 km or ≥40 km to referral facility), and randomly assigned clusters (1:1) to use intervention (n=45) or control treatment (n=45). Sites, participants, and field monitors were aware of their study assignment. The primary outcomes were all-cause neonatal mortality within 28 days post-partum and all-cause neonatal mortality within 28 days post-partum among babies who survived the first 24 h of life. Analysis was by intention to treat. Neonatal mortality rate was compared with generalised estimating equations. This study is registered atClinicalTrials.gov (NCT01241318 ). Findings: From Feb 15, 2011, to Jan 30, 2013, we screened 42 356 pregnant women and enrolled 39 679 women (mean 436·2 per cluster [SD 65·3]), who had 37 856 livebirths and 723 stillbirths; 63·8% of deliveries were facility-based. Of livebirths, 18 450 (99·7%) newborn babies in the chlorhexidine group and 19 308 (99·8%) newborn babies in the dry cord care group were followed up to day 28 or death. 16 660 (90·0%) infants in the chlorhexidine group had chlorhexidine applied within 24 h of birth. We found no significant difference in neonatal mortality rate between the chlorhexidine group (15·2 deaths per 1000 livebirths) and the dry cord care group (13·6 deaths per 1000 livebirths; risk ratio [RR] 1·12, 95% CI 0·88–1·44). Eliminating day 0 deaths yielded similar findings (RR 1·12, 95% CI 0·86–1·47). Interpretation: Despite substantial reductions previously reported in south Asia, chlorhexidine cord applications did not significantly reduce neonatal mortality rates in Zambia. Chlorhexidine cord applications do not seem to provide clear benefits for newborn babies in settings with predominantly facility-based deliveries and lower (<30 deaths per 1000 livebirths) neonatal mortality rates. Funding: Bill & Melinda Gates Foundation.